Protein profile of seminal plasma and functionality of spermatozoa during the reproductive season in the common carp (Cyprinus carpio) and rainbow trout (Oncorhynchus mykiss) - Shaliutina-Kolešová, Anna; Kotas, Petr; Štěrba, Jan; Rodina, Marek; Dzyuba, Borys; Cosson, Jacky; Linhart, Otomar (Molecular reproduction and development, 2016)
The purpose of the study was to analyze seminal plasma composition, sperm production, and sperm motility over the course of the spawning season in the common carp (Cyprinus carpio) and rainbow trout (Oncorhynchus mykiss). The highest mean percent of motile sperm (carp, 98.3 ± 1.6%; rainbow trout, 92.8 ± 5.6%) and highest spermatozoon velocity (carp, 286.3 ± 7.8 μm sec-1 ; rainbow trout, 245.3 ± 8.3 μm sec-1 ) were observed in the middle phase of the spawning period, at 5 sec post-activation. Sperm volume and concentration increased in the early spawning period, then decreased significantly toward the end of the season in both species. Seminal plasma osmolality was 262-270 mOsmol kg-1 from carp and 232-248 mOsmol kg-1 from rainbow trout, with little variation over the spawning period. Protein concentration in carp seminal plasma was stable throughout the reproductive season, whereas the highest protein level (2.1 ± 0.3 mg mL-1 ) in rainbow trout was observed in the middle phase of the spawning period. Seminal plasma composition in both species was analyzed using two-dimensional polyacrylamide gel electrophoresis combined with mass spectrometry. Thirteen differentially expressed protein spots in carp seminal plasma and sixteen spots in rainbow trout seminal plasma varied over the course of the reproductive season. The unique proteins identified are involved in the regulation of spermatogenesis, sperm motility, maintenance of sperm membrane lipid stability, and antioxidant protection. These results provide a deeper understanding of the role of fish seminal plasma proteins as well as a list of novel markers of sperm quality. Mol. Reprod. Dev. 83: 968-982, 2016 © 2016 Wiley Periodicals, Inc.
Keywords: mužské pohlaví; Fish Proteins; kapři; sperma; Carps; Oncorhynchus mykiss; Seminal Plasma Proteins; zvířata; Male; Semen; rybí proteiny; Animals; proteiny semenné plazmy